An investigation of adoption intention of halal traceability system among food SMEs - Kamarulzaman, Nitty Hirawaty; Muhamad, Nur Aminin; Mohd Nawi, Nolila (Emerald Group Publishing, 2021)
Purpose: The incredulity among Muslim consumers due to fake and doubtful halal logos has led to some querying the halal compliance and halal integrity among food small and medium enterprises (SMEs). By using the traceability systems consumers may track and trace the movement of food products available in the market. The purpose of this paper is to investigate factors that influence food SMEs’ intention to adopt a halal traceability system. Design/methodology/approach: A structured questionnaire survey was developed and administered to a systematic random sampling of 260 food SMEs. The data were analyzed using descriptive analysis, Chi-square analysis, Pearson correlation analysis and logistic regression analysis. Findings: The results revealed a strong correlation between the environmental aspect (EA) and perceived usefulness (PU) of a halal traceability system. Sales turnover, PU, perceived ease of use, technological aspect, organizational aspect and EA are the factors that influenced food SMEs’ intention to adopt a halal traceability system. Research limitations/implications: The context of this study is confined to the SMEs in the food industry in Peninsular Malaysia, thereby limiting the generalizability of the findings to other industries. Practical implications: This study shows a halal traceability system facilitates food SMEs in enhancing their business and provides tremendous potential to further improve the halal industry in Malaysia. Originality/value: The traceability system that is perceived to be easy and useful are the most influential factors toward the adoption of technology among food SMEs. Thus, this study confirms the growing importance of the halal traceability system in the food industry.